Internalization of Pancasila Values as an Effort to Prevent Corruption in Indonesia - Sriwidodo, Joko (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2023)
The problem of corruption in Indonesia is complicated. Even though, laws and regulations have been made that regulate sanctions for corruption, there are still many corruptors emerged. Various attempts were made to prevent and eradicate corruption, as a result all the efforts were in vain. So, it is necessary to research discusses "Internalization of Pancasila Values as an Effort to Prevent Corruption Crimes in Indonesia". The purposes in this research are to describe the efforts of Indonesia government to resolve corruption that have been implemented so far in Indonesia and to analyze the internalization of Pancasila values as an effort to prevent corruption in Indonesia. This research uses a descriptive normative research method with a qualitative approach. The results of this research are that various efforts are needed to resolve corruption in Indonesia. There are several efforts to eradicate corruption, including through preventive, deductive and repressive strategies. Corruption has an impact on various aspects such as corruption can hinder development, the economy, and weaken the character of the Indonesian nation. Therefore, to deal with corruption, the Indonesian people must further strengthen the values of Pancasila in their personalities and in their daily lives. As for the internalization of Pancasila values in the prevention of corruption in the form of moral and legal norms through the system at various levels of education and learning.